Structural and Spatial Planning for Category D Hospitals - Feriandy, Dicky Ilham; Hayati, Allatifah Nurul; Larasati, Niken; Firmanto, Arief (Pelopor Publikasi Akademika, 2025)
Structural and spatial planning for category D hospitals to be considered feasible both structurally and in terms of quality requirements, must be guided by SNI 1726:2019 and Regulation of the Minister of Health of the Republic of Indonesia No.24 of 2014. Hospital D is a hospital with basic health services and is located in rural or remote areas and is the first referral from the community health center. In addition to planning, a building structure analysis is also carried out and as an illustration of whether the building is safe after analysis. Details and dimensions of the plates, beams, columns, and foundations are also sought. There are 2 methods used for this planning, namely quantitative and qualitative methods, with secondary data. Planning data is determined starting from the overall function of the building, the number and function of each floor, the type of structure, the height of the building, the height of each floor, and the roof covering. The planning made consists of structural components in the building including plates, beams, columns, and foundations. The material used in the building is concrete with a quality of 20.05 MPa, while the quality of the reinforcing steel used is 420 MPa. Modeling and analysis of the hospital building structure was carried out using ETABS 16 software, while for structural visualization using AutoCAD 2014 software. The loads entered were dead load, live load, wind load, and earthquake load.